Blood pressure, Blood Sugar, Smokers and their Relationship with Physiological Variables of Some Risk Factors - Nada Saad Naji Al-Taee (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study deals with the physiological measurements of fasting blood sugar (FBG), clinical blood pressure (CBP) and smokers and their association with risk factors (obesity, gender and age) among university students. A total of 257 students (77 females and 180 males) were registered. Including 41 healthy and 42 students who were FBG; 33 were healthy and 69 were suffering from CBP; 39 non smokers and 33 students who were smokers; aged 19-26 years. A statistically not-significant connection was found between FBG, CBP and smoking with obesity rates; but a significant difference between smoking and CBP with age and gender, respectively. These findings highlight the prevalence of FBG and CBP also smoking in students and its relation to certain risk factors such as obesity, sex and age among selected student groups.